Food Commodity Inspection Technique and Safe Food Consumption in the Hospitality Industry in Delta State: Teknik Inspeksi Komoditas Pangan dan Konsumsi Pangan yang Aman di Industri Perhotelan di Negara Bagian Delta - ugo chuks okolie; Tuemu Clement; Ayewumi Tamarasere Ejiroghene (Metafora: Education, Social Sciences and Humanities Journal, 2026)
This study investigates the application of food commodity inspection techniques in ensuring safe food consumption within the hospitality industry in Delta State, Nigeria. With the growing demand for hotel, restaurant, and catering services, food safety has emerged as a critical concern due to its direct impact on public health and business reputation. The study specifically examines key stages of the food supply chain, including sourcing, procurement, storage, handling, and service, to assess how inspection practices mitigate contamination risks. Data were collected from 200 respondents, comprising hospitality workers, regulatory officials, and consumers, using questionnaires and interviews, and analyzed through descriptive statistical and qualitative methods. Findings reveal that while a majority of establishments procure food from certified suppliers and implement proper storage and handling practices, gaps remain in informal sourcing, inconsistent adherence to hygiene standards, and limited staff training. The study further highlights the importance of systematic inspection methods, adherence to Hazard Analysis and Critical Control Points (HACCP) guidelines, and modern traceability systems in promoting food safety. Based on the results, recommendations are made for strengthening supplier verification, enhancing storage and handling practices, providing continuous staff training, and leveraging cost-effective technological solutions. Overall, the study underscores that robust food commodity inspection practices are essential for safeguarding consumer health and sustaining operational excellence in the hospitality sector.